Contaminated land guidance : the route to sustainable economic solutions - Strange, Jo; Langdon, Nick; Large, Alex (ICE Publishing, 2016)
'Contaminated Land Guidance' provides authoritative guidance and up-to-date information on the challenges associated with contamination on brownfield developments.